Epistemologi Inkar Al-Sunnah: Telaah Pemikiran Kassim Ahmad - Benny Afwadzi (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2018)
This article analyzes the epistemology of the inkar al-sunnah (sunnah pengingkar), which specializes in the study of Kassim Ahmad, a Malaysian Malaysian thinker. Epistemologically, he rejects the existence of the hadith of the Prophet with three sources of knowledge, namely empirical, rational, and revelation. But unfortunately, even though he was passionate about